2016
DOI: 10.1007/s11130-016-0532-y
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Use of Fermented Chickpea and Faba Bean Flour as Food Ingredients

Abstract: Apart from being a rich and inexpensive protein source, legumes provide essential vitamins, minerals and dietary fibre. Considering the nutritional benefits, legumes flour can potentially be incorporated in the development of new products. The aim of this study was to investigate whether fermentation affects the protein content, in vitro protein digestibility, trypsin inhibitor activity and the functionality of proteins in faba bean, desi and kabuli chickpea. Australian grown chickpea and faba bean were select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
78
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(86 citation statements)
references
References 29 publications
7
78
0
1
Order By: Relevance
“…Additionally, the hydrophilic surface formed through hyphae production by fungi during fermentation aided in greater binding of water, and offers a mechanistic explanation. Similar studies have reported improved WHC of chickpea, red bean, black‐eyed pea, oil bean, and Moringa oleifera flours through fermentation (Akubor & Chukwu, ; Chandra‐Hioe et al, ; Chawla et al, ; Oloyede, Ocheme, Chinma, & Akpa, ; Reyes‐Moreno, Cuevas‐Rodriguez, Milan‐Carrillo, Cardenas‐Valenzuela, & Barron‐Hoyos, ; Xiao et al, , ). The WHC increase in fermented flours was attributed to fermentation altering the protein conformation through proteolytic activity.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…Additionally, the hydrophilic surface formed through hyphae production by fungi during fermentation aided in greater binding of water, and offers a mechanistic explanation. Similar studies have reported improved WHC of chickpea, red bean, black‐eyed pea, oil bean, and Moringa oleifera flours through fermentation (Akubor & Chukwu, ; Chandra‐Hioe et al, ; Chawla et al, ; Oloyede, Ocheme, Chinma, & Akpa, ; Reyes‐Moreno, Cuevas‐Rodriguez, Milan‐Carrillo, Cardenas‐Valenzuela, & Barron‐Hoyos, ; Xiao et al, , ). The WHC increase in fermented flours was attributed to fermentation altering the protein conformation through proteolytic activity.…”
Section: Resultsmentioning
confidence: 62%
“…Previous studies have evaluated the effect of SSF on FC and FS of legume and cereal flours (Adebowale & Maliki, ; Chandra‐Hioe, Wong, & Arcot, ; Chawla et al, ; Elkhalifa, Schiffler, & Bernhardt, ; Xiao et al, ). Xiao et al () reported no significant difference in FC of fermented red bean flour (RBF) compared to unfermented red bean flour, whereas FS of fermented RBF was found to be higher than in the unfermented sample.…”
Section: Resultsmentioning
confidence: 99%
“…Fermentation has been shown to be efficient method to significantly reduce total polyphenol and tannin contents, and to markedly increase IVPD in pearl millet (Elyas and others ; El Hag and others ; Onyango and others ), sorghum flour (El Hag and others ; Onyango and others ; Osman and Gassem ), and beans (Chandra‐Hioe and others ). The fermentation‐induced increase in IVPD is attributed to enzymatic breakdown of complex storage proteins into simpler soluble products during fermentation, as well as a contribution from microflora proteolytic enzymes.…”
Section: Food Processing Methods For the Reduction Of Antinutritionalmentioning
confidence: 99%
“…Fermentation can inhibit the catalysis of digestive enzymes and promote protein cross‐linking. Protease secreted during fermentation can degrade protein, thus improving the digestibility of protein in vitro (Çabuk et al, ; Chandra‐Hioe, Wong, & Arcot, ). This was also confirmed by the increase in amino acids content during fermentation (Table ).…”
Section: Resultsmentioning
confidence: 99%